Pearl Millet Crop Husbandry - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This brochure is a guide to the cultivation of pearl millet, covering crucial aspects such as ideal climatic conditions, land preparation, optimal fertilizer and manure application, weed management, proper harvesting and post-harvest handling. It further delves into the nuances of pest and disease management, specifically addressing concerns like head mold from various fungi, stem borers, African ballworm and challenges posed by birds and Striga weeds. Practical control measures are provided for each production constraint experienced, emphasizing preventive strategies and recommended control measures to ensure successful cultivation and maximize crop yield.